Mitogen and lymphokine stimulation of heat shock proteins in T lymphocytes. - Ferris, D K (1988)
We have examined the effects of phytohemagglutinin (PHA) and the polypeptide growth factor interleukin 2 (IL-2) on the synthesis of the 70- and 90-kDa heat shock proteins (HSP70 and HSP90, respectively) in human T lymphocytes. Resting T cells (G0) stimulated with PHA responded with a generalized increase in protein synthesis that included HSP70. Gel blot analysis indicated that steady-state levels of HSP70 mRNA were not specifically modulated by PHA. Synthesis of HSP90 protein, however, peaked very rapidly following PHA stimulation and decreased sharply after 1 hr. When IL-2-dependent human T cells, synchronized by IL-2 deprivation, were treated with IL-2, synthesis of HSP70 mRNA was increased as much as 15-fold. HSP70 and HSP90 protein synthesis increased significantly upon IL-2 stimulation of human T lymphocytes. Two distinct members of the ancient family of heat shock genes, HSP70 and HSP90, are shown to be stimulated at the activation and progression stages of lymphocyte mitogenesis, which suggests that genetic mechanisms evolved from primitive stress/adaptation responses may be conserved in mammalian cellular activation.